Modernization and culture in Azerbaijan: second half of the XIX century: beginning of the XX century - Suleymanli, Mubariz (Linguistics and Culture Review, 2021)
The end of the 19th century and the beginning of the 20th century, characterized by the expansion of enlightenment, development of education, press and art in Azerbaijan, marked by many cultural events, went down in history as the formation of national thought and national statehood. But these facts have been ignored for many years, and were presented from a subjective and biased point of view during the Soviet times. However, the cultural heritage of that period, especially the reforms implemented in 1918-1920 to give equal rights to all citizens, regardless of ethnic, religious and political affiliation, gender, state attributes and reforms in education, science and culture, restored the state independence of the Azerbaijan people. In this sense, the study of cultural processes and modernization in Azerbaijan, including cultural reforms during the Azerbaijan Democratic Republic (1918-1920) is relevant both in the terms of studying historical experience and the successful implementation of cultural construction and integration into the world in modern times. The main purpose of the study is to explore the cultural basis of the process of historical renewal and modernization in Azerbaijan, to use the results of this experience in building a modern democratic civil society.